Answer:
The correct answer is option C
(f o g)(x) = 3x² + 7x + 2
Step-by-step explanation:
<u>Points to remember</u>
<u>Composite functions</u>
Let f(x) and g(x) be the two functions then (f o g)(x) can be written as
(f o g)(x) = f(g(x))
<u>To find the value of (f o g)(x)</u>
Here f(x) =x + 2 and g(x) = 3x² + 7x
(f o g)(x) = f(g(x))
= f(3x² + 7x)
= 3x² + 7x + 2
Therefore the correct answer is option C
(f o g)(x) = 3x² + 7x + 2
total = 2372* (1+0.045)^20=
2372*1.045^20=
2372 * 2.411714025= 5720.585
she will have 5720.59 in 20 years
Answer:
y=x-1
Step-by-step explanation:
Answer:
-14
Step-by-step explanation:
Replace the 2 for each k.
![\frac{1}{4}2^{5} - 3k^{3} + k^{2} - k](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D2%5E%7B5%7D%20-%203k%5E%7B3%7D%20%2B%20k%5E%7B2%7D%20-%20k)
then solve it using PEDMAS: exponents first
= -14
Avocado out!!!!!!!!